Chemical Analysis of Lipid Boundaries after Consecutive Growth and Division of Supported Giant Vesicles - Lopez, Augustin (iScience, 2020)
The reproduction of the shape of giant vesicles usually results in the increase of their “population” size. This may be achieved on giant vesicles by appropriately supplying “mother” vesicles with membranogenic amphiphiles. The next “generation” of “daughter” vesicles obtained from this “feeding” is inherently difficult to distinguish from the original mothers. Here we report on a method for the consecutive feeding with different fatty acids that each provoke membrane growth and detachment of daughter vesicles from glass microsphere-supported phospholipidic mother vesicles. We discovered that a saturated fatty acid was carried over to the next generation of mothers better than two unsaturated congeners. This has an important bearing on the growth and replication of primitive compartments at the early stages of life. Microsphere-supported vesicles are also a precise analytical tool.